Immunocytochemical Localization of Enzymes Involved in Dopamine, Serotonin, and Acetylcholine Synthesis in the Optic Neuropils and Neuroendocrine System of Eyestalks of Paralithodes camtschaticus - Kotsyuba, Elena; Dyachuk, Vyacheslav (Frontiers in Neuroanatomy, 2022)
Identifying the neurotransmitters secreted by specific neurons in crustacean eyestalks is crucial to understanding their physiological roles. Here, we combined immunocytochemistry with confocal microscopy and identified the neurotransmitters dopamine (DA), serotonin (5-HT), and acetylcholine (ACh) in the optic neuropils and X-organ sinus gland (XO-SG) complex of the eyestalks of Paralithodes camtschaticus (red king crab). The distribution of Ach neurons was studied by choline acetyltransferase (ChAT) immunohistochemistry and compared with that of DA neurons examined in the same or adjacent sections by tyrosine hydroxylase (TH) immunohistochemistry. We detected 5-HT, TH, and ChAT in columnar, amacrine, and tangential neurons in the optic neuropils and established the presence of immunoreactive fibers and neurons in the terminal medulla in the XO region of the lateral protocerebrum. Additionally, we detected ChAT and 5-HT in the endogenous cells of the SG of P. camtschaticus for the first time. Furthermore, localization of 5-HT- and ChAT-positive cells in the SG indicated that these neurotransmitters locally modulate the secretion of neurohormones that are synthesized in the XO. These findings establish the presence of several neurotransmitters in the XO-SG complex of P. camtschaticus.